Suspended matter and its components in the western Black Sea - Sergey V Vostokov (PANGAEA, 1996)
Distribution and composition of suspended matter in the western Black Sea is examined in relation to influence of river run-off and eutrophication. Changes in suspended matter concentration and composition within the studied area are shown to be caused principally by intensity of production processes associated with different levels of eutrophication of coastal waters. Data on suspended matter obtained aboard or by remote control from space satellites are analyzed as a basis for evaluation of eutrophication scales and monitoring for evolution of marine production processes.
Supplement to: Vostokov, SV (1996): Suspended matter as a measure of productivity in the western Black Sea. Translated from Okeanologiya, 1996, 36(2), 260-267, Oceanology, 36(2), 241-247